Sol-gel derived (Ba,Sr)TiO$_3$ thin films for tunable devices - Czekaj, D.; Lisińska-Czekaj, A.; Orkisz, T.; Osińska, K.; Kozielski, L. (Archives of Acoustics, 2006)
The present study is devoted to synthesis and investigation of basic properties of ferroelectricthin films. The sol-gel-type chemical solution deposition method was used for preparationof (Ba$_{0.6}$Sr$_{0.4}$)TiO$_{3}$ (BST) thin films. The thin films were characterized in terms oftheir microstructure, crystalline structure, chemical composition and dielectric properties. Itwas found that the BST thin films adopted cubic crystallographic symmetry of the spacegroup $Pm3m$, whereas the chemical composition of the thin films corresponded well with thechemical composition of the solution. Complex impedance spectroscopy was used to measurefrequency-dependent dielectric properties of the thin films. Due to the high tunability andlow dielectric loss, great application potential of these ferroelectric thin films was consideredespecially as tunable dielectric devices.